Radical Orthodox Economics - McMullen, Steven (Christian scholar's review, 2014)
Steven McMullen notes that in recent years, a number of theologians and philosophers, following John Milbank, have drawn on continental post-modern philosophy to form a critique of capitalism and modern economics. Often called the “Radical Orthodoxy” movement, these scholars argue that the problems with capitalism lie not with its results, but its underlying metaphysics and ecclesiology. This essay summarizes these arguments, draws on the work of Christian economists to argue that many of the concerns of the movement are shared by scholars in the economics profession, and concludes by proposing four fruitful avenues of inquiry that could advance a “Radical Orthodox Economics.”